Lumbar Disc Replacement for Junctional Decompensation After Fusion Surgery: Clinical and Radiological Outcome at an Average Follow-Up of 33 Months - Hähnle, Ulrich R. (SAS J, 2007)
BACKGROUND: Failed fusion surgery remains difficult to treat. Few published data on disc replacement surgery after failed fusion procedures exist. Our objective was to evaluate outcomes of junctional lumbar disc replacement after previous fusion surgery and to correlate outcome with radiological changes to parameters of sagittal balance. METHODS: Out of a single-center prospective registry of 290 patients with 404 lumbar disc replacements, 27 patients had had a previous lumbar fusion operation on 1 to 4 lumbar segments and had completed a mean follow- up of 33 months (range: 18–56). We correlated the clinical outcome measures (patient satisfaction, 10-point pain score, and Oswestry Disability Index [ODI] score) to parameters of spinal sagittal alignment (sacral tilt, pelvic tilt, pelvic incidence, and lumbar lordosis). RESULTS: Postoperative hospital stay averaged 3.3 days (range: 2–8). Previously-employed patients went back to their jobs with a mean of 32 days (range: 21–42) after the procedure. At the latest follow-up, 1 of the patients considered the outcome to be poor, 3 fair, 8 good, and 15 excellent. Twenty-four patients “would undergo the operation again.” Average pain score decreased from 9.1 ± 1.0 (SD) to 3.2 ± 2.1 (P < .01). Average ODI decreased from 50.2 ± 9.9 preoperatively to 21.7 ± 14.2 (P ≤ .01). We found the change in pelvic tilt to be an independent predictor of better clinical outcome by multivariate analysis (P < .05). CONCLUSIONS: In patients with junctional failure adjacent to a previous posterolateral fusion, disc replacement at the junctional level(s), compared with osteotomy and fusion surgery, offers the advantage of maintaining segmental mobility and correcting the flat-back deformity through a single approach with less operative time and blood loss. Early- to intermediate-term results are promising. The influence of changes in spinal sagittal alignment on clinical outcome needs to be addressed in future research. CLINICAL RELEVANCE: This is the first study on “junctional disc replacement patients” correlating clinical outcome to changes in spinal/pelvic alignment.